2016
DOI: 10.1177/1948550616652209
|View full text |Cite
|
Sign up to set email alerts
|

Embodying Power

Abstract: Adopting expansive (vs. contractive) body postures may influence psychological states associated with power. The current experiment sought to replicate and extend research on the power pose effect by adding another manipulation that embodies power—eye gaze. Participants ( N = 305) adopted expansive (high power) or contractive (low power) poses while gazing ahead (i.e., dominantly) or down at the ground (i.e., submissively). Afterward, participants played a hypothetical ultimatum game, made a gambling decision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In recent times several social priming/embodied effects came under scrutiny, e.g., cleanliness priming (Johnson et al, 2014), elderly priming (Doyen et al, 2012) or power posing (Garrison et al, 2016; online databases tracking their recent replications are PsychFileDrawer.org and CurateScience.org). Overall, we do not concur with the position that the effects of embodied cognition are in general doubtful.…”
Section: General Conclusionmentioning
confidence: 99%
“…In recent times several social priming/embodied effects came under scrutiny, e.g., cleanliness priming (Johnson et al, 2014), elderly priming (Doyen et al, 2012) or power posing (Garrison et al, 2016; online databases tracking their recent replications are PsychFileDrawer.org and CurateScience.org). Overall, we do not concur with the position that the effects of embodied cognition are in general doubtful.…”
Section: General Conclusionmentioning
confidence: 99%
“…The preregistration format, rather than inhibiting scientific discovery or exploration, actually then points researchers to the next direction for their research, while at the same time making it clear to the reader that such obtained effects were exploratory and not confirmatory. Prior to our special issue, there were other attempts to replicate the power pose effect (Garrison, Tang, & Schmeichel, 2016;Ranehill et al, 2015). Ranehill et al could not replicate the effect on hormonal level, but found the manipulation to influence felt power.…”
mentioning
confidence: 99%
“…It also increased participants’ testosterone levels – the hormone associated with dominance – and decreased afternoon cortisol levels, the hormone associated with responsiveness to stress. After performing the high power poses, participants also engaged in more risky gambling behavior (Carney et al, 2010, however, the latter two effects were not replicated (Ranehill et al, 2015; Garrison et al, 2016). In line with the associated meaning interpretation, Cesario and McDonald (2013) found the effects of expansive power poses on risk-taking behavior only when the poses were performed in a social context: when participants watched photographs of other people while holding the poses.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, assuming expansive poses elicited feelings of power in Western participants, but not in East Asian participants (Park et al, 2013). In some studies, performing ‘power poses’ did not influence psychological sense of power (e.g., Garrison et al, 2016). …”
Section: Introductionmentioning
confidence: 99%